(untitled) (Journal of Environmental Microbiology and Toxicology, 2022)
Plant extracts have been studied extensively for their ability to suppress the growth of bacteria. Because these findings were not reported on in the benchmark values, it was not possible to compare the results of this study to other investigations. Nonlinear regression analysis of the data is one of the most accurate methods of determining this value. The Minimum Non-inhibitory concentration (NIC) and inhibitory concentration (MIC) values of the methanolic extract of Allium sativum against the pathogen Aeromonas hydrophila were successfully determined using Lambert and Pearson’s modified Gompertz model. Using nonlinear regression is useful since the 95% confidence interval of the MIC and NIC can now be estimated. As shown by the model’s high correlation coefficient (0.995), garlic’s MIC and NIC values (28.02 mg/mL, 95% Confidence Interval from 26.42 to 29.71 mg/mL) and (12.60 mg/mL, 95% Confidence Interval from 11.88 to 13.37 mg/mL) suggest that it could be used as an inhibitory agent against this essential fish pathogen.